1998
DOI: 10.1074/jbc.273.39.25393
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the Functional Site of α-Dendrotoxin

Abstract: We identified the residues that are important for the binding of ␣-dendrotoxin (␣DTX) to Kv1 potassium channels on rat brain synaptosomal membranes, using a mutational approach based on site-directed mutagenesis and chemical synthesis. Twenty-six of its 59 residues were individually substituted by alanine. Substitutions of Lys 5 and Leu 9 decreased affinity more than 1000-fold, and substitutions of Arg 3 , Arg 4 , Leu 6 , and Ile 8 by 5-30-fold. Substitution of Lys 5 by norleucine or ornithine also greatly alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 66 publications
(41 reference statements)
2
56
0
Order By: Relevance
“…37-41), they are all likely to bind to the P-region of Kv1 channels (32,(42)(43)(44)(45)(46). Recent progress has characterized the sites by which these peptides bind to the vestibule of Kv1 channels (14, 16 -17, 27, 32-33, 36, 47-50), and comparison of these sites revealed that all of these blockers possess at least a common diad composed of two functionally important residues: a lysine and an hydrophobic residue (32,36). A model of the interaction of these blockers with Kv1 channels is now commonly accepted in which this critical lysine plugs the pore of the channel (14 -17, 27).…”
Section: Contribution Of the Diad Lys-25/tyr-26 In The Bgkmentioning
confidence: 99%
See 1 more Smart Citation
“…37-41), they are all likely to bind to the P-region of Kv1 channels (32,(42)(43)(44)(45)(46). Recent progress has characterized the sites by which these peptides bind to the vestibule of Kv1 channels (14, 16 -17, 27, 32-33, 36, 47-50), and comparison of these sites revealed that all of these blockers possess at least a common diad composed of two functionally important residues: a lysine and an hydrophobic residue (32,36). A model of the interaction of these blockers with Kv1 channels is now commonly accepted in which this critical lysine plugs the pore of the channel (14 -17, 27).…”
Section: Contribution Of the Diad Lys-25/tyr-26 In The Bgkmentioning
confidence: 99%
“…Indeed, it was previously proposed that in BgK, Lys-25 and Tyr-26 constitute the two elements of a critical diad formed by a lysine and a spatially close hydrophobic residue (aromatic or aliphatic) found in all Kv1 channels blockers from sea anemone, snakes, and scorpions (32,36). In order to evaluate the functional contribution of the diad, we synthesized the analog possessing both substitutions, K25A/Y26A.…”
Section: Contribution Of the Diad Lys-25/tyr-26 In The Bgkmentioning
confidence: 99%
“…DTX-K (26) was synthesized using the same procedure as for ␣DTX (25). Synthetic charybdotoxin (ChTX) was purchased from Latoxan (Valence, France).…”
Section: Methodsmentioning
confidence: 99%
“…25. Protein concentration was determined according to Lowry, using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation